Isolasi dan Penapisan in Vitro Aktinomiset untuk Mengendalikan Xanthomonas - Yuvika Yuvika; Aswardi Nasution; Abdul Gafur (Jurnal Fitopatologi Indonesia, 2013)
Nursery disease frequently found on Acacia crassicarpa seedlings is bacterial leaf blight caused by Xanthomonas sp. Disease symptom starts as a small fleck on the leaf which may then develop to leaf strike or leaf blight if the environmental factors are conducive to disease development. Actinomycetes are soil microorganisms that produce biologically active substances such as enzymes and antibiotics. These compounds could inhibit growth of other microorganisms, particularly bacteria. Thus, Actinomycetes are considered as potential candidates of biocontrol agents for plant pathogens. In the current study Actinomycetes isolated from a wide range of localities were screened for their efficacy against Xanthomonas sp. in vitro. The objective of this study was to obtain Actinomycete isolates effective against Xanthomonas, to mitigate impact of the pathogen on quality of A. crassicarpa seedlings. All Actinomycete collections were isolated from soil by a chain of enrichment isolation procedures. The antibiotic activities were investigated through antimicrobial screening tests using paper discs on assay plates. Of the 75 Actinomycete isolates originally collected and screened, 5 isolates showed good antimicrobial activities against Xanthomonas and are therefore considered as potential biocontrol agent candidates.